A Pyrene‐Pyrazole‐Based Rotamer Senses Hg2+ on the Nanomolar Scale. Issue 8 (14th March 2017) - Naskar, Barnali; Dhara, Anamika; Modak, Ritwik; Maiti, Dilip K.; Prodhan, Chandraday; Chaudhuri, Keya; Requena, Alberto; Cerón‐Carrasco, José Pedro; Goswami, Sanchita
Abstract: In this experimental and theoretical study, a new pyrene‐pyrazole based chemosensor, 5‐Methyl‐1H‐pyrazole‐3‐carboxylic acid pyren‐1‐ylm ethylene hydrazide (MpcphH), is designed and prepared for selective sensing of Hg 2+ . Photophysical studies, including UV‐vis and fluorescence, showed thatMpcphH exhibited high selectivity and sensitivity in response to Hg 2+ with detection limit in the nano molar range. The 1 H and 13 C−NMR spectroscopic techniques are presented to elucidate the coordination modes ofMpcphH towards Hg 2+ . The relative stability of the ketoimine/imineol tautomers and the specific rotamer responsible for Hg 2+ coordination are evaluated by means of DFT calculations. Furthermore, MpcphH provides a reliable approach to monitor cellular cytoplasmic Hg 2+ in HepG2 cells. Abstract : A new pyrene‐pyrazole based chemosensor is reported that selectively senses Hg 2+ in nano molar range at the physiological pH and cellular cytoplasmic Hg 2+ in HepG2 cells. The relative stability of the specific rotamer responsible for Hg 2+ coordination are evaluated by means of DFT calculations.